Oral health as a gateway to overall health and well‐being: Surveillance of the geriatric population in the United States. (14th May 2019) - Hung, Man; Moffat, Ryan; Gill, Gagandeep; Lauren, Evelyn; Ruiz‐Negrón, Bianca; Rosales, Megan N.; Richey, James; Licari, Frank W.
Abstract: Aims: Little evidence exists to confirm that better oral health is associated with better overall health and well‐being. The present study aimed to examine the impact of oral health on the overall health of the population greater than 65‐year old in the entire United States. Methods and results: Data from National Health and Nutrition Examination Survey (NHANES) 2015–2016 were used. Variables included demographics and perceptions of oral health and overall health and well‐being. Weighted prevalence estimates were calculated using mean, standard deviation, and percentage as appropriate. Chi‐square tests and logistic regressions were performed to examine the association of oral health with physical health, mental health, general health, and systemic disease conditions. Analyses showed statistically significant relationships between oral health, physical, mental and general health, energy levels, work limitation, depression, and appetite. Out of the 10 systemic diseases being investigated, six of them were directly related to oral health outcome. Conclusion: This study provided strong empirical evidence that oral health is directly associated with different disease conditions and contributes largely to an individual's general health, particularly in the elderly. In the current landscape of patient‐centered and value‐based care, addressing the oral health needs of the elderly, who generally find themselves with limited access to care, should be a priority.